2010
DOI: 10.1007/s11433-010-4207-7
|View full text |Cite
|
Sign up to set email alerts
|

Modeling study of residence time and water age in Dahuofang Reservoir in China

Abstract: Understanding the dynamics of water renewal in a reservoir is essential when the transport and fate of dissolved substances are evaluated. A three-dimensional hydrodynamic model was implemented to compute average residence time and water age in Dahuofang Reservoir in China. The model was verified for a one-year time period in 2006. A simulation reproduced intra-annual variation of mixing represented by the fall/winter mixing and the spring/summer stratification. The simulated variation of vertical thermal stru… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
7
0
1

Year Published

2011
2011
2018
2018

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 26 publications
(9 citation statements)
references
References 43 publications
1
7
0
1
Order By: Relevance
“…This approach not only takes advantages of finite-element methods for grid flexibility and finite-difference methods for numerical efficiency but also provides a good numerical representation of momentum, mass, salt, and heat conservation. It has been successfully applied to many water bodies such as estuaries, lakes, and coastal bays [15][16][17][18][19][20][21]. The hydrodynamic model is introduced and described.…”
Section: Physical Modelmentioning
confidence: 99%
“…This approach not only takes advantages of finite-element methods for grid flexibility and finite-difference methods for numerical efficiency but also provides a good numerical representation of momentum, mass, salt, and heat conservation. It has been successfully applied to many water bodies such as estuaries, lakes, and coastal bays [15][16][17][18][19][20][21]. The hydrodynamic model is introduced and described.…”
Section: Physical Modelmentioning
confidence: 99%
“…The issue of drinking water security plays a decisive role in the national economy and social wellbeing in China [2,3]. With the enormous development of aquaculture, water pollution in reservoirs has become a serious problem with the water quality of drinking water source directly influencing people's health, which is related to the economic development and stability of the general social situation.…”
Section: Introductionmentioning
confidence: 99%
“…Many studies have indicated that the inflow discharges will affect the variations of pollutants or nutrients in reservoirs [3][4][5][32][33][34]. As the backup drinking water source reservoir for Changde City in China, the Huangshi Reservoir, with multiple tributaries, is currently suffering from the threat of eutrophication, with the influence of pollutants or nutrients from the tributaries of Huangshi Reservoir having not been taken into consideration.…”
Section: Introductionmentioning
confidence: 99%
“…Water age, which is defined as ''the time that has elapsed since the particle under consideration left the region in which its age is prescribed as being zero" (Delhez et al, 1999), is a useful indicator for the temporal and spatial quantification of the transport time of pollutants (Takeoka, 1984;Boynton et al, 1995;Delhez et al, 1999;Shen and Wang, 2007;Li et al, 2011). The concept of water age has been extensively applied in coastal water areas with intense water exchange, which is induced by tides and wind (Deleersnijder et al, 2001;Liu and Huang, 2009;Liu et al, 2012), and lakes and reservoirs with intense water movement, which is induced by human regulations Shen et al, 2011;Wu et al, 2013). These studies also explored the dominant controlling factors of water age, such as the inflow/outflow and wind.…”
Section: Introductionmentioning
confidence: 99%